The Pygmalion Effect to Piano Teaching From the Perspective of Educational Psychology - Qi, Wen; Dong, Xingru; Xue, Xiaoran (Frontiers in Psychology, 2021)
Aiming at the problem of low student enthusiasm in piano teaching, this work tries to apply “Pygmalion effect” to piano teaching from the perspective of educational psychology. With experimental research as the means, 45 students are chosen from 9 classes in grade 2, 4, and 6 of a central elementary school in Beijing City, and the experimental group and the control group are set up. Questionnaire is adopted to conduct the pre-test and post-test of the experiment to analyze the factors that affect the students’ attitude towards music learning, as well as the effect of piano teaching. The results show that the Pearson correlation coefficient (two-tailed) between the piano teacher’s encouragement level and the students in the piano course is 0.427**, indicating that the piano teacher’s encouragement level and the students’ enthusiasm in the piano course are significantly correlated at the 0.01 level. The Pearson correlation coefficient (two-tailed) between student confidence level and piano learning activity is 0.276**, indicating that there is a significant correlation between self-efficacy and student piano learning enthusiasm at the 0.01 level. The pre-test and post-test results show that the students in the experimental group of each grade generally perform much better in piano learning than the students in the control group, which proves that the Pygmalion effect can play an excellent intervention role in piano teaching. In this research, the value of “Pygmalion effect” in the educational psychology of piano music education in primary schools is deeply studied to explore the possibility of a novel piano teaching model. The research results show that teacher encouragement can stimulate students’ subjective initiative and make students perform better in piano learning. This research provides reference and ideas for the combination of education and psychology related research in music classroom.